2012
DOI: 10.1111/j.1365-3164.2012.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double‐blinded placebo‐controlled study to evaluate an effective ciclosporin dose for the treatment of feline hypersensitivity dermatitis

Abstract: Results suggest that 7.0 mg/kg ciclosporin once daily in food or per os for 6 weeks is effective and well tolerated in feline HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 17 publications
7
60
0
2
Order By: Relevance
“…This was first verified by assessing the response to various interventions, with the observation that the SCORFAD values decreased in parallel with the administration of interventions that had increasing anti‐inflammatory effect (i.e. placebo and ciclosporin at 2.5 and 7.0 mg/kg) 19 . Furthermore, the sensitivity of this scale to change depended upon the selected outcome measures.…”
Section: Discussionmentioning
confidence: 96%
“…This was first verified by assessing the response to various interventions, with the observation that the SCORFAD values decreased in parallel with the administration of interventions that had increasing anti‐inflammatory effect (i.e. placebo and ciclosporin at 2.5 and 7.0 mg/kg) 19 . Furthermore, the sensitivity of this scale to change depended upon the selected outcome measures.…”
Section: Discussionmentioning
confidence: 96%
“…Ciclosporin has been used for many years in the treatment of feline hypersensitivity dermatitis at various doses, generally ranging from 5 to 10 mg/kg . The dose of 7 mg/kg given daily has recently been tested in a randomized, blinded parallel group, placebo‐controlled study and was shown to be efficacious and well tolerated . In cats with head and neck excoriations, self‐induced alopecia, eosinophilic plaque and/or miliary dermatitis, the administration of 7 mg/kg ciclosporin daily for 6 weeks resulted in a decrease in total lesion and owner‐assessed pruritus severity scores.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment at a dose of 7 mg/kg for up to 6 weeks was shown to be efficacious and well tolerated. 4 The current study, including a large population of cats, shows that following 7 mg/kg per day of CsA for a minimum of 4 weeks, the frequency of CsA administration could be reduced to EOD while maintaining control of HD in >70% of treated cats. The dosing frequency could be further reduced to TW in 53% of treated cats.…”
Section: Discussionmentioning
confidence: 89%
“…4 An overall assessment of clinical response (scored from 0 to 4) was made by the investigator and the owner at each visit of the phase 2 study beginning at V2.…”
Section: Assessment Of the Clinical Responsementioning
confidence: 99%